Dose effects of ultraviolet and terahertz laser radiation on the plasma membrane of erythrocytes - Лариса Січевська; Тетяна Овсяннікова; Ірина Забєліна; Аліна Коваленко; Олександр Левченко; Олег Гурін (Біофізичний вісник)
Background: In modern medicine, various technical means and developments are actively used in invasive intravascular (IVL) and non-invasive transcutaneous blood irradiation methods, including low-intensity laser radiation (LLLR) of various ranges. Despite the positive clinical results of such exposure, the physical and molecular mechanisms remain incompletely understood. Ultraviolet (UV) and terahertz (THz) ranges of electromagnetic radiation are classified as biogenic; therefore, establishing their effects at the level of blood cells will allow them to be recommended for use in medical and biotechnological practice after the development of appropriate exposure methods.